Neuritogenic Activities of Various Kappaphycus alvarezii Extracts in Hippocampal Neurons - Gabriel Tirtawijaya; Maria Dyah Nur Meinita; Md. Nazmul Haque; Il So Moon (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2021)
The carrageenophyte Kappaphycus alvarezii seaweed is known to have neuritogenic activities. Post-harvest treatment of seaweed affects its biological activities. Five drying treatments of K. alvarezii, including oven-drying, sun-drying, freeze-drying, shade-drying, and salting followed by shade-drying, were evaluated for their effects on neuritogenic activities. We also evaluated the neuritogenic activity of different parts of K. alvarezii thalli and its carrageenan waste. Neuron cells of the 19th day pregnant rat fetuses were collected from the hippocampus by brain dissection. Neuron cells were isolated by dissociation of the hippocampal tissue. Cells were plated onto poly-DL-lysine-coated glass coverslips in 24-well plates and treated with extracts. All tested extracts were obtained from maceration using 95% ethanol. Freeze and shade-drying extracts exhibited significantly higher neuritogenic activities (p 0.05) compared to that of the vehicle control. Carrageenan waste also significantly promoted the neuritogenic activities (p 0.05) with an optimal dose at 1 µg mL-1. Old and young thalli showed insignificant differences in neuritogenic activities. The carrageenan waste extract retained neuritogenic activities. Thus, the utilization of carrageenan waste for neuritogenic material provides added value to the waste in the carrageenan industry. Freeze and shade dried K. alvarezii can be used as a neuritogenic agent to provide optimum biological activity.